Optical coherence tomographic (OCT) evaluation of intraoral non‐ablative erbium: YAG laser (SMOOTH mode) in rejuvenation of nasolabial folds; A prospective randomized split face comparative pilot study. Issue 3 (3rd December 2019) - Moftah, Nayera; Samy, Nevien; Allam, Riham S. H. M.; El Tagy, Shaza A. H.; Abdelghani, Rania
Abstract: Background: There are both few non‐comparative studies investigating the efficacy of intraoral Er: YAG laser (SMOOTH mode) in rejuvenating nasolabial folds (NLFs) and lack of valid and objective wrinkles scales. In this prospective randomized split face comparative pilot study, we investigated the safety and efficacy of intraoral Er: YAG laser (SMOOTH MODE) compared with extraoral approach in rejuvenating NLFs using OCT as an objective evaluating tool. Materials and Methods: Twenty adult women with notable NLFs were randomized in this study. The patients received 5 monthly sessions of Er: YAG laser (SMOOTH mode) using intraoral approach on one side and extraoral approach on the other side. Outcome was evaluated 2 weeks and 4 months post‐treatment by Global Aesthetic Improvement Scale (GAIS), OCT, and patients' satisfaction. Side effects were also evaluated. Results: Intraoral sides had significant increase in OCT evaluated dermal thickness at 4 months post‐treatment ( P  = .03) without side effects compared with extraoral sides. Extraoral approach had significantly higher patients' satisfaction compared with intraoral approach at 2 weeks and 4 months post‐treatment ( P  = .03, .02, respectively). Insignificant differences between both approaches were found regarding GAIS scoring, OCT evaluated epidermal thickness at 2 weeks and 4 months post‐treatment, and OCT evaluated dermal thickness at 2 weeks post‐treatment ( P  < .05). Conclusion: Intraoral Er: YAG laser (SMOOTH mode) is safer and more effective than extraoral approach in rejuvenating NLFs. OCT is a promising objective tool for evaluating facial wrinkles. Further studies are still needed.